Witch & wizard - Patterson, James; Charbonnet, Gabrielle (New York : Vision, 2011)
A sister and brother, along with thousands of young people, have been kidnapped and either thrown in prison or turned up missing after accusations of witchcraft were made against them, and the ruling regime will do anything in order to suppress life and liberty, music and books.
Keywords: Kidnapping -- Fiction; Suspense fiction